O “tradicional” e o “contemporâneo” no choro: um estudo etnomusicológico entre rodas e palcos de chorões de Belo Horizonte - Paulo Vinícius Amado (2020)
During my own experience both as a musician and as a researcher in the choro (Brazilian popular music) scenario in Belo Horizonte, capital of Minas Gerais/Brazil, words such as “traditional” and “contemporary” were frequently used by the chorões (choro musicians) themselves to describe and distinguish their music making, therefore pointing out to the idea as well as to the existence of a “traditional choro” and of a “contemporary choro” in the city. There is a great number of events promoted by chorões in Belo Horizonte, nowadays. They happen daily, weekly; on stages and in the casual rodas, and all this allows us to consider, at first, an almost inherent diversification of this musical practice according to the singularities of the various locations where it is performed. From this scene emerges the understanding of these defining words of musical practices, which are balanced between being similar and distinct. The extension of such a thought contemplates, moreover, the pertinence of this research, which intends to contribute to the understanding of those musical-cultural characteristics of the choro, by means of an ethnomusicological study. The research focused especially on the occasions and implications of the uses of certain concepts of “tradition” and “contemporaneity” linked to the musical performances of chorões in Belo Horizonte. The use of these concepts is defined in their discourses by means of the words and the expressions “traditional choro” and “contemporary choro”. From a multi-situated ethnographic work, while walking around with people that perform choro and that think about their performances, dialogues, descriptions and notes about such musical manifestations said to be traditional or contemporary were developed, seeking to understand what makes them similar or divergent, and also – with the aid of some literature – how these concepts appeared or were invented so as to refer to the musical making of chorões in Belo Horizonte.